Development of an integrated logistics information system for third party logistics facilitators. (17th February 2006) - Choy, K.L.; So, Stuart C.K.; Lau, Henry C.W.; Kwok, S.K.; , Felix T.S. Chan
Third Party Logistics (3PL) service is one of the core logistics services in the local logistics industry nowadays. However, the business operation among the small and medium-sized 3PL facilitators and their trading partners is still manual-based which is inefficient. Hence, there is a need to develop new approach for them. In this paper, a comprehensive logistics information management platform called Integrated Logistics Information Management System (ILIMS) is proposed to suit this need. It aims to integrate the internal and external logistics' operations and the information flow of 3PL facilitators providing them a systematic mean of doing business. Moreover, it provides an effective channel for them to communicate with different trading partners without geographical restriction at low operating cost. A case study of a local 3PL facilitator is discussed to demonstrate the application of ILIMS. By using this generic system, the performance of both the 3PL facilitator and their suppliers are improved significantly.